Design and development of automatic drum deheader - Ahmad Nazaruddin, Mat Zin (2008)
Industrial drums are one of the types of packaging to protect goods for the consumers. When the drums already been use, the drum will become the hazardous waste for the environment. To prevent it happened, recycling play an important role for the Industrial drums. However, there is lacks of equipment and technology to reuse the old materials such as drums. This project presents a design of low cost an automatic drum deheader prototype by using less expensive materials. Designing and fabrication is the main process to develop this automatic drum deheader prototype. The end product from the research is the prototype of automatic drum deheader where the cutting method to cut the outside chimes is presented, so that the most metal drum covers can be removed without having to beat down the covers. This prototype had been developed for easily adjust the height and thickness of chime to accommodate with various drum and chime configurations. These prototypes also capable to complete one rotation around the drum in less than one minute like the other drum deheader available in market. The new design of automatic drum deheader prototype in this project basically is a simple design, lightweight and cheaper compare with others drum deheader. As a summary, the development of automatic drum deheader in this project is successfully done and research for the further improvement need to carry out to make this product more effective